Disruptive Communication as a Means to Engage Children in Solving Environmental Challenges: A Case Study on Plastic Pollution - Löfström, Erica; Richter, Isabel; Nesvold, Ine H. (Frontiers in Psychology, 2021)
Environmental degradation and how we care for our planet are some of the greatest challenges the world is up against at this moment. These challenges has received increased focus in both, research and the public sphere. So far, most of this attention revolved around adult’s attitudes and behavior. However, environmental engagement amongst the younger generation gains in popularity. Using plastic pollution as a case, this qualitative study aims to acquire insights into the mental models of children. We collected qualitative data during an innovative, structured workshop according to the “Nature In Your Face” (NIYF) framework. The approach challenges the assumption that the societal change can be achieved gradually, with non-invasive techniques. Instead, we explore the potential of disruption to push citizens out of their comfort zone, thereby making room for co-creation. The disruption was performed by confronting 36 fifth graders from a Norwegian primary school, with disturbing images of plastic contaminating their local shorelines. The data was obtained by using the workshop framework, combined with semi-structured group interviews. The interview data was analyzed by means of thematic analysis. We found that the disruptions triggered emotional reactions like anger and fear. With these emotions as a driving force, the first workshop step was introduced, the Framing of the problem. The next step, Twisting the problem, was reflected in the children developing their own, creative solutions and creatively engaged with them in groups. The last step, Using, was only touched upon in the workshop and is therefore beyond the scope of this paper. Our results indicate that there are three prominent themes reflecting how children discuss plastic pollution. The children talked about their 1) Emotions related to plastic pollution, 2) Attitudes related to plastic, and 3) Perceptions of plastic pollution. These themes were further subdivided into different types of emotions, characteristics of plastic as a material as well as perceptions on different locations of unnecessary plastic. Psychologically, the mechanisms underlying the identified themes were linked to eco-anxiety, denial, self-efficacy and cognitive dissonance. We conclude that disruptive eco-visualization can create an emotional response amongst children, which can be transformed into co-creation of ideas.